Parallel curriculum units for grades K-5 - Imbeau, Marcia B. (Corwin Press, a Sage Company, 2011)
The empirically based Parallel Curriculum Model shows teachers how to create meaningful, emotive, and engaging curriculum that challenges all learners according to their interests and abilities.